AI-Powered Personalized Learning: Assessing Its Impact on Academic Achievement and Development in Students with Disabilities - Deepti Sharma; Archana B. Saxena; Deepshikha Aggarwal (Language, Literature and Education: Research Updates Vol. 3, 2025)
The integration of Artificial Intelligence (AI) into special education has the potential to revolutionize learning experiences for students with diverse disabilities, including cognitive, sensory, and motor impairments. This paper explores the efficacy of AI-driven adaptive learning systems in personalizing educational pathways, enhancing cognitive development, and improving academic performance in students with special educational needs. This study investigates the application of Artificial Intelligence (AI) in special education, focusing on how AI-driven adaptive learning systems can personalize learning experiences for students with disabilities. Utilizing a dataset of 100 students with special educational needs, including categories such as Dyslexia, Autism, and Motor Impairment, this research aims to evaluate the impact of AI interferences on learning progress over a three-month period. The dataset includes various features such as initial learning progress, engagement levels, feedback quality, and learning outcomes after 3 months of AI-based involvement. Through machine learning techniques, including regression (linear regression) and classification models (decision tree), the study analyzes how initial learning progress and other variables predict students’ improvement in academic performance after using AI tools. The results demonstrate a statistically significant improvement in the academic progress of students with special needs, with AI intrusions leading to measurable gains in learning outcomes across all categories. The findings suggest that AI can effectively support individualized learning paths, enhance student engagement, and improve academic achievement, thereby contributing to a more inclusive and personalized educational experience. This paper emphasizes the potential of AI in transforming special education by making learning more adaptive and accessible, offering valuable insights for educators, policymakers, and technology developers aiming to foster educational equity.